2018
DOI: 10.1001/jamapediatrics.2017.4938
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the School-Based Telemedicine Enhanced Asthma Management (SB-TEAM) Program on Asthma Morbidity

Abstract: Poor adherence to recommended preventive asthma medications is common, leading to preventable morbidity. We developed the School-Based Telemedicine Enhanced Asthma Management (SB-TEAM) program to build on school-based supervised therapy programs by incorporating telemedicine at school to overcome barriers to preventive asthma care. OBJECTIVE To evaluate the effect of the SB-TEAM program on asthma morbidity among urban children with persistent asthma. DESIGN, SETTING, AND PARTICIPANTS In this randomized clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
157
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(162 citation statements)
references
References 42 publications
3
157
0
2
Order By: Relevance
“…An a priori stratification by asthma severity showed a substantial improvement in CASI scores amongst those with more severe asthma following the intervention. These findings are consistent with observations made with other school‐based intervention strategies 7,9–11,17 . In a comparison of two recent school‐centered asthma programs, one strategy focused on providing a nurse‐centered school‐based asthma intervention on children with high risk for an asthma exacerbation identified by uncontrolled asthma or a recent asthma exacerbation while another program focused its efforts on providing once‐daily inhaled corticosteroid using a school‐based intervention program 10,11 .…”
supporting
confidence: 84%
See 1 more Smart Citation
“…An a priori stratification by asthma severity showed a substantial improvement in CASI scores amongst those with more severe asthma following the intervention. These findings are consistent with observations made with other school‐based intervention strategies 7,9–11,17 . In a comparison of two recent school‐centered asthma programs, one strategy focused on providing a nurse‐centered school‐based asthma intervention on children with high risk for an asthma exacerbation identified by uncontrolled asthma or a recent asthma exacerbation while another program focused its efforts on providing once‐daily inhaled corticosteroid using a school‐based intervention program 10,11 .…”
supporting
confidence: 84%
“…Where health care delivery in conventional settings has failed to address these well‐documented disparities, innovative delivery models in communities, schools, and homes that address social determinants of health have made some inroads 7–11 . It is clear that health care delivered in a silo is not effective, and strategies that move the needle on addressing common barriers to access to high‐quality care are needed.…”
mentioning
confidence: 99%
“…Four studies observed less health care utilization, which may translate to a decrease in cost and disease burden 10,12,15,18. Health care utilization includes emergency department visits, ambulatory visits, hospitalizations, and urgent care visits.…”
Section: Resultsmentioning
confidence: 98%
“…In addition to implementing supervised asthma therapy programs, supplemental interventions were concurrently integrated in 4 studies, including a tobacco reduction program for smoke-exposed children,14 counseling sessions incorporating motivational interviewing techniques,13 and peak flow meter monitoring 17,18. School-based telemedicine visits were conducted to ensure appropriate assessment, preventive medication prescription, and follow-up care in 1 study 12. Web-based technology was utilized in 2 studies 11,17.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation